2019
DOI: 10.4236/ajps.2019.105051
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Drought Tolerance in Two Apple Cultivars Associated with Difference in Leaf Morphology and Anatomy

Abstract: Apple is one of the most important fruit trees in temperate zones, and is cultivated widely throughout the world. Drought stress affects the normal growth of apple tree, and further affects fruit yield and quality. The present study examined the effects of drought on photosynthesis and water use efficiency (WUE) of two apple cultivars (Honeycrisp and Yanfu 3) that differ in drought tolerance. The results showed that the photosynthetic rate decreased in response to drought stress for both cultivars, with signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Moreover, water use efficiency defines the relationship between photosynthesis and transpiration (P n /E). According to the literature, an increase in WUE under water stress conditions is associated with an adaptation to deficit irrigation, while WUE reduction is associated with sensitive species [42][43][44]. However, plants with low WUE were more competitive in arid environments because they consumed more resources more rapidly thus suppressing competitors.…”
Section: Gaseous Exchangementioning
confidence: 99%
“…Moreover, water use efficiency defines the relationship between photosynthesis and transpiration (P n /E). According to the literature, an increase in WUE under water stress conditions is associated with an adaptation to deficit irrigation, while WUE reduction is associated with sensitive species [42][43][44]. However, plants with low WUE were more competitive in arid environments because they consumed more resources more rapidly thus suppressing competitors.…”
Section: Gaseous Exchangementioning
confidence: 99%
“…is one of the most economically important fruits worldwide, and China is the world’s largest apple producer. Given that most apple trees are grown in arid or semi-arid regions, drought is considered the main environmental factor restricting apple production and thus the development of the apple industry [ 1 , 2 ]. The study on the yield of ‘Fuji’ under drought stress found that moderate drought stress and severe drought stress resulted in a reduction of 9.34% and 22.94% in yield per plant, respectively [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis is one of the physiological processes which is sensitive to environmental stresses (Johnson et al, 2015). It has been reported that drought inhibits photosynthesis through stomatal limitation and non-stomatal limitation (Barchet et al, 2014;Bai et al, 2019). Stomatal closure is one of the earliest responses of plants to drought stress, reducing transpiration and photosynthetic rate (Chaves et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…is one of the most economically important fruits worldwide, with the largest area of cultivation in China (Liu et al, 2012). Most apple trees are grown in arid or semi-arid regions, and drought is considered as the main environmental factor restricting the development and production of apples (Bai et al, 2019). The development of drought resistance is a priority goal in apples.…”
Section: Introductionmentioning
confidence: 99%